Environmental favourable foundries through maintenance activities - A. Saniuk; M. Jasiulewicz-Kaczmarek; A. Samolejova; S. Saniuk; R. Lenort (Metalurgija, 2015)
Maintenance today contributes to the aim of sustainable development in society, including environmental and energy saving, safety and economical aspects. The main purpose of the paper is to present the role of maintenance in the realization of sustainable developing practices in a foundry industry. Maintenance offers numerous opportunities to reduce the influence of foundry processes on the natural environment and utilize resources more efficiently. Maintenance activities can help to reduce losses and thereby improve the efficiency of the processes used in the production of resources (e.g. raw materials, energy, etc.), especially in areas such as: the choice of an appropriate strategy for the maintenance of machinery and equipment (e.g. reactive, preventive, proactive); inventory management of spare parts; lubrication management and management of technology media.